Peran Manajemen Sumber Daya Manusia dalam Upaya Peningkatan Manajemen Pengetahuan - Reza Muhammad Rizqi (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2022)
The role that Human Resource Management (HR) plays in the process of enhancing knowledge management is investigated in this study. This research investigates the ways in which HRM practices contribute to improved knowledge management operations. In order to collect data, a survey was conducted, and interviews were conducted with a total of 12 informants from SMEs (UKM). According to the findings of the study, HRM practices offer initiative in the process of improving the knowledge management strategies that companies use. It is possible to draw the conclusion that each HRM sub-component has an effect on the knowledge management component. Furthermore, HRM is very influential and has a positive effect on the quality management process in the workplace and vice versa